Dapagliflozin in diabetic kidney disease patients with different filtration status - Yang, Yang; Li, Manna; Zou, Honghong; Yang, Pingping; Wang, Li; Xu, Gaosi (European journal of pharmaceutical sciences, 2025)
Few studies have discussed the effects and mechanism of dapagliflozin on diabetic kidney disease (DKD) with different glomerular filtration rate (GFR) and systolic blood pressure (SBP). This study aimed to investigate the variation in the eGFR and proteinuria after dapagliflozin treatment in DKD patients with different filtration status and SBP levels. First, we conducted a cross-sectional study to determined hyperfiltration threshold for the DKD trial. Then, we enrolled 259 DKD patients with an eGFR greater than 70 mL/min/1.73m2 and an albumin-to-creatinine ratio (ACR) between 30 and 200 mg/g to receive treatment with dapagliflozin. Hyperfiltration was defined as the 95th percentile of eGFR above the age- and gender- specific in healthy subjects, DKD patients were divided into hyperfiltration and non-hyperfiltration groups, and SBP > 120 mmHg and ≤ 120 mmHg groups. The eGFR, ACR, and blood and urine electrolytes were measured before and after treatment. The mean eGFR change at 2 weeks in the hyperfiltration with SBP > 120 mmHg group was greater than in the non-hyperfiltration with SBP ≤ 120 mmHg group (P = 0.048). The mean ACR reduction values were greater in the non-hyperfiltration with SBP ≤ 120 mmHg group than in the hyperfiltration with SBP > 120 mmHg group at 12 weeks (P = 0.042). There was no difference in other blood or urine electrolytes before and after treatment, except for the fractional excretion of sodium (FENa), which significantly increased after 2 weeks (P < 0.001) and recovered after 8 weeks (P = 0.305). DKD with non-hyperfiltration with SBP ≤ 120 mmHg had a lower mean eGFR decline and greater decrease in the ACR after treatment. The initial increase in FENa and subsequent decrease after dapagliflozin treatment may be the main mechanism behind the eGFR variation. [Display omitted]